Students’ experience in marketing communication through social media/ Nani Ilyana Shafie ... [et al.] - Shafie, Nani Ilyana; Abd Rahman, Nurul Hayani; Ismail, Shaira; Mohammad, Noorita; Mohd Shariff, Balqis (Unit Penerbitan Universiti Teknologi MARA Perak Branch, 2023)
Experiential learning has gained prominence as a practical pedagogical approach in contemporary education. A total of 32 students enrolled in the Marketing Communication course, using social media as a marketing communication tool to provide a more interactive and practical application of knowledge. For the course, students worked in pairs and were assigned to choose a brand of product or service in any industry, create mock influencer campaigns, and analyze the chosen brand’s social media content to determine how it could be improved. It highlights the use of social media platform applications in the Marketing Communication subject with the aim of improving the student’s learning experience by turning fact-driven content into an engaging learning activity. At the end of the course, students were required to prepare an infographic, a reflective assignment, and video content. The students’ experiential learning improves their ability to identify marketing communication strategies, engage audiences, and foster a deeper understanding of consumer behaviour.